G463(P) A Rare cause of encephalopathy – a case report. (24th May 2017) - Talbot, A; Singh, D; White, M; Sundararajan, S
Abstract : Introduction: Lead toxicity is becoming an increasingly rare cause of encephalopathy in children. We report a case of encephopathy due to lead poisoning. Case Summary: A 2 year old boy was admitted to paediatric ward with vomiting, poor feeding, history of pica (ingestion of wood-work) and speech delay. He improved following intravenous fluids and was discharged. Seven days later he required PICU admission due to prolonged seizure. He was extubated following a normal CT brain. MRI brain, performed due to fluctuating GCS, showed diffuse signal abnormality. An underlying metabolic disorder was considered and further investigations were performed. On day 4 he deteriorated with signs of raised ICP, focal seizures and apnoea's. Following stabilisation and instigation of neuro-protective measures, repeat CT confirmed signs of raised ICP. On day 5, blood lead results confirmed a severely toxic level of 11.47micromol/L. He received chelation therapy for 7 days. Despite reduction in blood lead levels he made no neurological recovery and his care was re-orientated. Conclusion: Severe intoxication of lead (>3.38 micromol/L) is a medical emergency. GI symptoms associated with lead poisoning can often mimic those of a viral illness. Differentials should include lead poisoning particularly in children with a history of pica and microcytic anaemia. Chelation should be commenced before confirmation in the presence of elevated zinc protoporphyrin, basophilic stippling of RBCs, lead flecks on abdominal radiograph or lead lines on long-bone radiographs. References: Liu J, et al . Blood lead concentrations and children's behavioural and emotional problems: a cohort study. JAMA Pediatr . 2014 Aug;168 (8):737–45. Gordon RA, et al . Aggressive approach in the treatment of acute lead encephalopathy with an extraordinarily high concentration of lead. Arch Pediatr Adolesc Med . 1998;152(11).